Methodology to establish stability regions for controllers performance. Case of study: Sliding mode controllers - Camacho, Oscar; Rojas, Rubén; González, Luis (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This work shows the development of a method to analyze the robustness of a controller based on the establishment of stability regions. Based on computer simulations a data set is obtained for a wide range of modeling parameter variations. On each case, controller parameters are adjusted up to reach the stability limit. The resulting data is used to obtain boundary equations that establish the stability regions. The proposed method was used to study a sliding mode controller robustness based on a first order plus deadtime model of the process (POMTM). This model represents most of the overdamped processes such as chemical processes.